The breadwinner [videorecording (DVD)] - Ellis, Deborah, 1960- (Universal Pictures Home Entertainment, 2018)
Parvana is an eleven-year-old girl growing up under the Taliban in Afghanistan in 2001. When her father is wrongfully arrested, Parvana cuts off her hair and dresses like a boy in order to support her family. Working alongside her friend Shauzia, Parvana discovers a new world of freedom, and danger. With undaunted courage, Parvana draws strength from the fantastical stories she invents, as she embarks on a quest to find her father and reunite her family.